ANALISIS KOMPARASI KINERJA KEUANGAN BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH SAAT PANDEMI COVID -19 - Maesaroh, Siti (JUBISMA, 2023)
Global economic growth in 2020 contracted by 3.5% from the previous growth of 2.8% in 2019. This contraction was caused by the Covid pandemic - 19 which is not only a health crisis but also a social and economic crisis. To reduce economic pressure due to the Covid-19 pandemic, governments around the world have issued massive and extraordinary stimuli in the form of fiscal stimulus, monetary stimulus, and relaxation policies in the financial services sector. The Covid-19 pandemic is a challenge for the business world, including Islamic banking and conventional banking in Indonesia. Financial performance is an important measure of whether there is an increase in financial companies or vice versa. The data used in this study is secondary data and uses quantitative methods at the time of the Covid-19 Pandemic. The study's results show that based on the average (mean) result of each ratio, the financial performance of Conventional Commercial Banks based on LDR/FDR, CAR, NOM/NIM, and NPL/NPF is better than Islamic Commercial Banks. Meanwhile, based on the BOPO and ROA ratios, the financial performance of Islamic Commercial Banks is better than Conventional Commercial Banks. Based on the results of the independent sample t-test, it is known that the six ratios have significant differences between the financial performance of Conventional Commercial Banks and Islamic Commercial Banks based on LDR/FDR, NPF/NPL.NOM/NIM, ROA, CAR, and BOPO